One of the approaches to the organization of the modern educational process - A. G. Savenko; Yu. A. Skudnyakov (Informatika)
This paper proposes a new approach to the creation and use of rotational-hybrid model of organizing a modern educational process representing the integration of educational, information communication, testing, management, rotational and other technologies. A visual and mathematical model, an diagram of information and educational system, an algorithm for the rotation of trainees are presented. An approach is proposed for constructing the optimal way to determine the maximum assimilation of disciplines by students in each set of studied disciplines and the formation of its most acceptable subset. The program-algorithmic implementation of the rotational-hybrid model in the form of a universal teaching-testing electronic learning tool is shown. The mathematical basis of the rotational-hybrid model is set theory using graph models, which compare favorably with other mathematical apparatus in visibility and a matrix form of representation that can be easily processed on a computer. The effectiveness of using the developed rotational-hybrid model and its algorithmic implementation is illustrated with the help of developed teaching-testing electronic teaching tool, introduced into educational process at the Department of Information Systems and Technologies of the Institute of Information Technologies of the Belarusian State University of Informatics and Radioelectronics.